ONLINE LEARNING FOR STUDENTS: IMPACT AND PERCEPTION - Vinny Stephanie Hidayat; Ita Salsalina Lingga; Jovi, Christian (ZILLZELL MEDIA PRIMA, 2024)
The aim of this research is to examine how online learning affects students' academic achievement. Online learning is expanding quickly at all levels of official education, including the university level. This study at one of Bandung, Indonesia's private university seeks to ascertain the impact of online learning on students' perceptions and academic achievement. All current participants in the Accounting Study Program make up the study's population. The class of 2018-2022 members of Accounting Study Program who are currently enrolled in or have completed the Auditing course make up the sample for this study. Purposive sampling is the sample selection technique employed, while the research approach used is explanatory research. Using the T and F tests, multiple regression analysis, and SPSS, the study hypothesis is tested. According to the sample technique, questionnaires were given out to 113 students. Additionally, interviews were conducted to find out what students thought of online learning, both positively and negatively. The study's findings indicated that online learning has an impact on academic achievement. Although most students have positive perceptions of online learning, there are some negative ones as well. However, the university can address these negative perceptions by correcting the relevant errors.